Snowflakes - Treahy, Iona (BBC Worldwide Publishing Ltd, 2003)
It's a cold day, and Pom finds a snowflake. But when she tries to show it to the other Fimbles, she discovers something unexpected.
Keywords: Action & Adventure; General; Juvenile Fiction